Influence of hydrogen import prices on hydropower systems in climate-neutral Europe - Richard Schmitz; Christian Øyn Naversen; Philipp Härtel (Energy Systems, 2023)
While climate and energy policy targets require fundamental changes and expansions in the energy infrastructure, hydropower systems across Europe remain essential for low-carbon energy systems. With renewable fuel import prices being subject to large uncertainties, this work aims to substantiate the relationship between these fuel import prices and multireservoir hydropower systems in a climate-neutral energy system. To that end, three green hydrogen import price scenarios are combined with two aggregated modelling approaches for pan-European hydropower assets. Using the integrated energy system model SCOPE~SD, the analysis shows that import prices for green hydrogen have a significant impact on European electricity generation (+~595~GW eland +~650~TWh el/yr), domestic hydrogen production (+~396~TWh th/yr), and water values of European hydropower assets (+~33~% of average value in Norway). The results further indicate that the different aggregation methods only have a minor impact, suggesting that the computationally more efficient approach with up to 90% reductions in solution time provides suitable approximations of hydropower generation and flexibility in future analyses.
Keywords: 330; Energy system modelling; Hydropower; Electricity market; Renewable fuels; Hydrogen; Aggregation